I can factor it?

Geometry Level 3

cos 2 ( x ) + cos 2 ( 2 x ) + cos 2 ( 3 x ) 1 = a k = 1 b cos ( k x ) \large \cos^2( x) + \cos^2( 2x) + \cos^2 (3x) - 1 = a \prod_{k=1}^b \cos( kx)

If the equation is true for all values of x x with constants a , b a,b ,what is the value of 2 a + b 2a+b ?


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

cos 2 x = 1 + cos 2 x 2 \cos^2x = \dfrac{1+\cos2x}{2}

cos 2 2 x = 1 + cos 4 x 2 \cos^22x = \dfrac{1+\cos4x}{2}

cos 2 3 x = 1 + cos 6 x 2 \cos^23x = \dfrac{1+\cos6x}{2}

So we can modify the L.H.S as

cos 2 x + cos 2 2 x + cos 2 3 x 1 = 1 + cos 2 x 2 + 1 + cos 4 x 2 + 1 + cos 6 x 2 1 = cos 2 x + cos 4 x + cos 6 x + 1 2 \cos^2x + \cos^22x + \cos^23x - 1= \dfrac{1+\cos2x}{2} + \dfrac{1+\cos4x}{2} + \dfrac{1+\cos6x}{2} - 1 = \dfrac{\cos2x + \cos4x + \cos6x + 1}{2}

cos 6 x + 1 = 2 cos 2 3 x \cos6x + 1 = 2\cos^23x

cos 2 x + cos 4 x = 2 cos x cos 3 x \cos2x + \cos4x = 2 \cos x \cos3x

L . H . S = ( 2 cos 3 x ) ( cos 3 x + cos x ) 2 = ( cos 3 x ) ( 2 cos x cos 2 x ) 1 L.H.S = \dfrac{(2\cos3x)(\cos3x + \cos x)}{2} = \dfrac{(\cos3x)(2\cos x \cos2x)}{1}

L . H . S = 2 k = 1 3 cos k x L.H.S = 2\displaystyle \prod_{k=1}^{3}\cos kx

a = 2 & b = 3 a = 2 \text{ \& } b = 3

2 a + b = 7 2a + b = \huge\color{#D61F06}{\boxed{7}}

Chew-Seong Cheong
Oct 24, 2015

cos 2 ( x ) + cos 2 ( 2 x ) + cos 2 ( 3 x ) 1 = cos 2 ( x ) + [ 2 cos 2 ( x ) 1 ] 2 + [ 4 cos 2 ( x ) 3 cos 2 ( x ) ] 2 1 = y 2 + 4 y 4 4 y 2 + 1 + 16 y 6 24 y 4 + 9 y 2 1 Let y = cos x = 16 y 6 20 y 3 + 6 y = 2 y ( 8 y 5 10 y 2 + 3 y ) = 2 y ( 2 y 2 1 ) ( 4 y 3 3 y ) = 2 cos ( x ) cos ( 2 x ) cos ( 3 ) = 2 k = 1 3 cos k x \begin{aligned} \cos^2 (x) + \cos^2 (2x) + \cos^2 (3x) -1 & = \cos^2 (x) + [2\cos^2 (x) -1]^2 + [4\cos^2 (x) - 3\cos^2 (x)]^2 -1 \\ & = y^2 + 4y^4 -4y^2 + 1 + 16y^6-24y^4 + 9y^2 - 1 \quad \quad \small \color{#3D99F6}{\text{Let }y = \cos x} \\ & = 16y^6 - 20y^3 + 6y \\ & = 2y(8y^5-10y^2+3y) \\ & = 2y(2y^2-1)(4y^3-3y) \\ & = 2\cos(x) \cos(2x) \cos(3) \\ & = 2\prod_{k=1}^3 \cos{kx} \end{aligned}

2 a + b = 2 ( 2 ) + 3 = 7 \Rightarrow 2a+b = 2(2) + 3 = \boxed{7} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...